Paumacariu kā kāvya saundarya: Mahākavi Svayambhū praṇīta mahākāvya Paumacariu ke mahattvapūrṇa saṃśoṃ kā kāvya-rūpāntaraṇa - Svayambhū.; Jaina, Miśrīlāla. (Apabhraṃśa Sāhitya Akādamī, 2005)
Verse and prose translation of selected epic poetry.
Verse and prose translation of selected epic poetry.
Hindi and Prakrit.